Transformasi Kualitas Audit Melalui Teknologi Disrupsi: Sintesis Literatur Sistematis atas Peran Kompetensi Auditor dan Blockchain - Kiky Anggrita; ⁠Naqiyyah Ghina; Sasha Salsabilah; Rina Tjandra Kirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
The transformation of audit quality in the era of technological disruption currently centers on the integration of blockchain and the pivotal role of auditor competency as a primary instrument to reduce agency costs. This study aims to map the opportunities, constraints, and strategic research agendas for the future of the auditing profession through a Systematic Literature Review (SLR) of 22 reputable scientific articles published between 2021 and 2026. Utilizing the lens of Agency Theory, the findings reveal a fundamental paradigm shift from conventional sample-based testing toward real-time data population examination. Leveraging blockchain through smart contracts significantly enhances the transparency and integrity of audit evidence, effectively mitigating information asymmetry between managers (agents) and shareholders (principals). However, the success of this monitoring mechanism is highly dependent on the technical capabilities of auditors in navigating big data governance and cybersecurity; inadequate competency may instead widen the gap in oversight failure. A key finding of this study emphasizes that while Artificial Intelligence (AI) improves the efficiency of routine tasks, professional skepticism remains the final safeguard in complex decision-making to protect the interests of capital owners. Practically, this synthesis serves as a strategic reference for regulators and public accounting firms to redesign auditing standards and training curricula to ensure a synergy between digital systems and the auditor's fiduciary responsibilities.